Twórczość А.P. Czechowa w recepcji S.N. Bułhakowa - Sobennikow, Anatolij (Studia Rossica Posnaniensia, 2011)
The article is devoted to Sergej Bulgakov’s reception of Chekhov. Bulgakov turned numerous times to the works of Russian writers, such as Gertsen, Dostoyevsky, Tolstoy and others. The public lecture ‘Chekhov as Thinker’ was given in the autumn of 1904 at the Tenishev College. It can be examined within the framework of Bulgakov's reception of Chekhov's writings. However, a more productive approach seems to lie elsewhere: the philosopher’s thoughts on Chekhov in the context of his transition ‘from Marxism to idealism’. In this sense, the lecture on Chekhov represents a sum total of sorts. Chekhov's heroes become for him an example of the discrepancy between the general level of culture and spiritual potential of personality. In Chekhov's artistic world, the accent is indeed placed on the individual's moral effort. Instead of putting forward demands to the world, Chekhov's heroes, such as Dymov (in Poprygunia, The Hopper), Misail Poloznev (in Моя жизнь, My Life), Nina Zarechnaja (in Chaika, The Seagull) and many others, begin with demands on themselves. The public lecture was given at the time of first Russian Revolution of 1905. Thus the philosopher extends the boundaries of aesthetic analysis, and considers Chekhov's oeuvre as a testament, while the personality of the writer becomes an example of civic service.